Civilian Population and Constructive Transformation of an Internal Armed Conflict: an Application to the Colombian Case - Alzate, Mónica; Universidad de Santiago de Compostela (Pontificia Universidad Javeriana, 2009)
The goal of this study is to explore a set of psychosocial variables that may contribute to the constructive transformation of a violent sociopolitical conflict. Based upon several authors in Social and Political Psychology, we propose an analysis of the conflict through thirteen variables. These variables are stated from the perspective of the non-combatant population within the context of a real armed conflict. The variables are related to beliefs about the conflict’s actors, perceptions of threat, confidence and costs, ethnocentric attitudes and interaction preferences with the adversaries. An attitude towards the conflict questionnaire was created and applied, with acceptable psychometric indexes. It confirms thirteen dimensions adjusted to the initial proposal